2022
DOI: 10.3389/fonc.2022.786981
|View full text |Cite
|
Sign up to set email alerts
|

Fat Attenuation Index of Renal Cell Carcinoma Reveals Biological Characteristics and Survival Outcome

Abstract: PurposeThe computed tomography fat attenuation index (FAI) is an ideal quantifiable imaging factor to identify the inflammation degree of peri-tumor adipose tissue. We aimed to verify whether FAI could reflect peri-tumor adipose inflammation, predict the survival outcome of renal cell carcinoma (RCC), and discover transcriptomic features of tumor tissues and adjacent adipocytes.Materials and MethodsTwo clinical cohorts (Fudan University Shanghai Cancer Center [FUSCC] cohort [n=129] and TCGA cohort [n=218]) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The prognostic significance of CT attenuation and FDG uptake of adipose tissue has yet to be evaluated in patients with cholangiocarcinoma. However, VAT HU and VAT SUV have been shown to be significant prognostic factors for predicting survival in other cancers in the abdominopelvic cavity, including colorectal cancer, gastric cancer, hepatocellular carcinoma, pancreatic cancer, and renal cell carcinoma, all of which grow in adipose tissue-dominant environments [11,12,14,15,23,24]. In the present study, among the adipose tissue imaging parameters, VSR, VAT HU, and VAT SUV were found to be significant predictors for RFS on univariate survival analysis, and VSR and VAT SUV remained as independent predictors for RFS on multivariate analysis after adjusting for age, sex, obesity, TNM stage, and extent of resection.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of CT attenuation and FDG uptake of adipose tissue has yet to be evaluated in patients with cholangiocarcinoma. However, VAT HU and VAT SUV have been shown to be significant prognostic factors for predicting survival in other cancers in the abdominopelvic cavity, including colorectal cancer, gastric cancer, hepatocellular carcinoma, pancreatic cancer, and renal cell carcinoma, all of which grow in adipose tissue-dominant environments [11,12,14,15,23,24]. In the present study, among the adipose tissue imaging parameters, VSR, VAT HU, and VAT SUV were found to be significant predictors for RFS on univariate survival analysis, and VSR and VAT SUV remained as independent predictors for RFS on multivariate analysis after adjusting for age, sex, obesity, TNM stage, and extent of resection.…”
Section: Discussionmentioning
confidence: 99%